A low‐profile dual‐band shorted patch antenna with enhanced‐bandwidth and multifunctional beams under reshaped modes. Issue 8 (30th April 2021) - Liu, Neng‐Wu; Liang, Yu‐Dong; Zhu, Lei; Zhou, Hao; Fu, Guang
Abstract: A low‐profile dual‐band shorted patch antenna (SPA) with bandwidth‐enhancement and multifunctional beams is proposed in this article. Initially, the radiation patterns of the traditional SPA are extensively studied. It demonstrates that the radiated fields of its TM1/2, 0, TM3/2, 0, and TM3/2, 1 modes are unsuitable to be employed for multibeam radiation. As such, a pair of shorting pins2 is loaded underneath the radiating patch, aiming to transform the broadside‐beam of TM1/2, 0 mode into the dual‐beam. After that, a set of shorting pins3 is placed to reshape radiated fields of its TM3/2, 0 and TM3/2, 1 modes as the dual‐beam and broadside‐beam, respectively. Meanwhile, the resonant frequencies of its TM1/2, 0 and TM1/2, 1 modes are reallocated closely to that of TM3/2, 0 and TM3/2, 1 modes. With these arrangements, both of impedance bandwidth and radiation beams are enhanced under quadruple‐mode resonance. Finally, the proposed SPA is fabricated and measured. The results illustrate that the microstrip patch antenna has successfully obtained an enhanced‐bandwidth (|S11 < −10 dB) ranging from 4.0 to 4.29 GHz and 5.24 to 5.77 GHz with two in‐band attenuation poles. Besides, a small thickness of about 0.04 free‐space wavelength is still maintained, while keeping single‐layer and single‐fed properties. Most importantly, the proposed SPA has generated desired broadside−/dual‐beam radiation patterns over the operating bands.